Process of Accumulation of Metal Ions on the Interior Surface of apo-Ferritin: Crystal Structures of a Series of apo-Ferritins Containing Variable Quantities of Pd(II) Ions - Ueno, Takafumi; Abe, Mizue; Hirata, Kunio; Abe, Satoshi; Suzuki, Masako; Shimizu, Nobutaka; Yamamoto, Masaki; Takata, Masaki; Watanabe, Yoshihito (Journal of the American Chemical Society, 2009)
Accumulation of metal ions on protein surfaces is an important subject in the field of materials science because these processes are applicable to the preparation of bioinspired inorganic materials. While previous studies related to this subject have focused on the preparation of nanomaterials using protein scaffolds, the detailed processes of metal ion deposition and metal core formation on a protein surface require clarification. Elucidation of the coordination structures of multinuclear metal binding sites on proteins at an early stage as well as intermediate and fully occupied stages of the metal ion deposition will help us to understand the reaction mechanisms so that desirable inorganic materials can be prepared using protein scaffolds. In this Article, we report on the detailed processes of accumulation of Pd(II) ions demonstrated by a series of X-ray crystal structural analyses of apo-ferritin (apo-Fr), an iron storage protein, containing different amounts of Pd(II) ions in the protein cage. We have identified the specific binding sites of Pd(II) ions and analyzed the dynamic changes in the coordination structure by a combination of the crystal structures and ICP quantitative analyses of apo-Fr containing low, intermediate, and high content of Pd(II) ions. Our studies on PdII·apo-Frs provide intriguing implications for the preparation of many other inorganic materials using protein surfaces.